2011
DOI: 10.1038/mi.2010.73
|View full text |Cite
|
Sign up to set email alerts
|

Langerin+ dendritic cells are responsible for LPS-induced reactivation of allergen-specific Th2 responses in postasthmatic mice

Abstract: Allergic asthma is a T cell-dependent inflammatory lung disease that results from complex interactions between genetic predisposition and environmental factors, including exposure to lipopolysaccharide (LPS). In this study, we have shown that airway LPS exposure was sufficient to induce airway hyperreactivity (AHR) and eosinophil recruitment in mice that had previously experienced an acute episode of allergic asthma. LPS-induced disease reactivation depended on the activation of allergen-specific CD4(+) T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…The role of lymphoid organ-resident Langerin + DC remains elusive, largely owing to their paucity in C57BL/6 mice (45), the most common background of transgenic and KO mice. Similarly, information on the prominent Langerin + DC population residing in the lung is sparse (23,24). The emerging and sometimes conflicting evidence of a functional specialization of epidermal LC and Langerin + dermal DC largely stems from in vivo cell-ablation experiments (1,46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of lymphoid organ-resident Langerin + DC remains elusive, largely owing to their paucity in C57BL/6 mice (45), the most common background of transgenic and KO mice. Similarly, information on the prominent Langerin + DC population residing in the lung is sparse (23,24). The emerging and sometimes conflicting evidence of a functional specialization of epidermal LC and Langerin + dermal DC largely stems from in vivo cell-ablation experiments (1,46).…”
Section: Discussionmentioning
confidence: 99%
“…Dermal Langerin + CD103 + DC are specialized in cross-presentation of cell-associated self-and viral Ag (21), a feature they share with lymphoid organ-resident CD8a + DC (22). In the lung, Langerin + CD103 + DC are essential for effective clearance of influenza virus infection (23) and responsible for reactivation of Th2 responses in postasthmatic mice (24). However, the molecular cues that confer LC and, in particular, the Langerin + CD103 + DC in the dermis and lung with their unique capacity to initiate regulatory and/or effector T cell responses remain elusive.…”
mentioning
confidence: 99%
“…Although it has not been identified that bacteria could directly cause allergic disease, the involvement of bacterial agents like LPS and flagellin in initiation of allergic inflammation has been recently documented (Hammad et al, 2009; Le et al, 2010; Ortiz-Stern et al, 2011; Prescott et al, 2008; Reginald et al, 2011; Yang et al, 2009). Based on the important role of DCs in immune response and the observation that TSLP is mainly produced by epithelial cells via TLR-mediated innate response (Kinoshita et al, 2009; Le et al, 2010; Ma et al, 2009), we hypothesized that DCs are capable of producing TSLP in response to microbial pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Using this system, it has been shown that the development of influenza virus-specific T cells is delayed, with consequent increased clinical severity and delayed viral clearance following influenza infection (GeurtsvanKessel et al, 2008). Depleting CD103 þ DCs in langerin-DTR mice also reduces eosinophil recruitment to the lung following LPS-treatment of animals that had been previously sensitized and challenged with the LACK (Leishmania analog of the receptors of activated C kinase) antigen (Ortiz-Stern et al, 2010). Although selective depletion of DC subsets in this way has great potential for improving our understanding of their function in vivo, we and others (Zammit et al, 2005) have found that DT can cause massive cell death and fatalities in mice.…”
Section: Cd103 D Dcsmentioning
confidence: 97%